Hydration Effects on Energy Relaxation of Ferric Cytochrome C Films after Soret-Band Photoexcitation - Ye, S. J.; Markelz, A. (Journal of Physical Chemistry B, 2010)
Protein hydration plays a critical role in protein dynamics and biological processes. Pump-probe transmission measurement has been applied to investigate the hydration effects on the energy relaxation of a heme protein ferric Cytochrome c (Cyt c) film after soret-band photoexcitation. Transient dynamics study indicates that the energy internal conversion time of similar to 300 fs is independent of hydration. The vibrationally excited electronic ground-state recovery rates show two transitions at the hydration level of h = 12.4-16.5% and 21.7-23.5%. The first transition occurs at the hydration level for the onset of an increasing ferric Cyt c flexibility while the second transition occurs at the saturated hydration level. The hydration dependence of steady-state electronic absorption spectrum results shows that the Q-band peak is nearly constant in center wavelength, but the line width surprisingly narrows with increasing hydration. For the similar to 695 nm absorbance associated with the MET80-Fe bond, the intensity increases with increasing hydration and slightly blue shifts. The 695 nm peak grows rapidly at h = 12.4% and then plateaus at h = 21.7%. This research shows that similar to 695 nm absorbance and ground-state recovery rates are sensitive to the hydration of the protein. This study will aid in understanding how hydration modulates the activity of the protein dynamics at a local level.
Keywords: Chemistry; circular-dichroism; conformation change; dynamics; ferricytochrome-c; protein hydration; resolved resonance raman; spectroscopy; unfolded states; vibrational-relaxation; water-molecules